MEKANISME PASAR DALAM PERSPEKTIF AL-GHAZALI DAN ALFRED MARSHALL: STUDI KOMPARATIF KONSEP HARGA, PERMINTAAN, DAN KESEIMBANGAN - Rachmawati, Tri Yulia (Investama : Jurnal Ekonomi dan Bisnis, 2026)
This study examines market mechanisms from the perspectives of two different figures: Al-Ghazali and Alfred Marshall, focusing on the concepts of price, demand, and equilibrium. The research background stems from the need to understand markets not only as technically functioning economic systems but also as social institutions requiring ethical and fair principles. The purpose of this study is to identify the similarities, differences, and relevance of Al-Ghazali and Marshall's thinking to the contemporary economic context. The method used is library research with content analysis techniques of relevant primary and secondary sources. The results show that Marshall views prices and market equilibrium as the result of the interaction of supply and demand that can be analyzed systematically. In contrast, Al-Ghazali emphasizes that price legitimacy and market stability must be within the framework of public interest, honesty, and the prevention of harmful practices such as fraud and hoarding. These findings emphasize that an ideal market mechanism must not only be efficient but also fair and oriented towards the public interest. Theoretically, this study offers a synthesis of two layers of equilibrium: technical (Marshall) and normative (Al-Ghazali). Practically, the results of this study can serve as a basis for strengthening market governance that integrates economic analysis with ethical values.